Potential Output Growth Estimates for Central America and the Dominican Republic - Garcia-Saltos, Roberto (IMF Working Papers; Working Paper, 2016)
This paper presents estimates of potential output for all Central American economies. Our findings are that potential output growth has declined in recent years in most economies of Central America. Lower capital accumulation and TFP growth are accounting for most of this decline. Apart from Costa Rica, there are no indications of significant economic slack in 2015 in Central America. Looking forward, potential growth in most Central American economies is expected to continue at an average of 4 percent in the medium-term due to structural constraints to capital and employment growth, and low TFP growth. Increasing potential growth, thus, should be a policy priority and structural reforms must be directed at improving business conditions, product and labor markets, and enhancing the capacity for innovation.